2020
DOI: 10.1177/0363546520962082
|View full text |Cite|
|
Sign up to set email alerts
|

Bankart Repair Versus Latarjet Procedure for Recurrent Anterior Shoulder Instability: A Systematic Review and Meta-analysis of 3275 Shoulders

Abstract: Background: Little consensus is available regarding the standard treatment for recurrent anterior instability of the shoulder. Typically, treatment selection has been based on training and tradition rather than the available evidence. Purpose: This study aimed to compare the clinical outcomes between arthroscopic Bankart procedure and the Latarjet procedure in the treatment of recurrent anterior shoulder instability with emphasis on follow-up time. Study Design: Systematic review and meta-analysis. Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 23 publications
(52 reference statements)
1
29
0
1
Order By: Relevance
“…The fi xation is performed using two cannulated screws (4). This type of operation provides excellent results with a low incidence of recurrences (5,6).…”
Section: Introductionmentioning
confidence: 95%
“…The fi xation is performed using two cannulated screws (4). This type of operation provides excellent results with a low incidence of recurrences (5,6).…”
Section: Introductionmentioning
confidence: 95%
“…119,120 A 2019 computational study using finite element models found an even lower threshold of 16% was the appropriate defect size to determine if bone augmentation was necessary. 121 Treatment choice is often based on training and tradition rather than available evidence, 62 which may leave high-risk patients vulnerable to recurrent instability, poor satisfaction, and additional procedures. The limited use of bone loss as a screening criterion for bone augmentation surgery may be an indication that patients are not adequately assessed for bone block procedures.…”
Section: Discussionmentioning
confidence: 99%
“… 74 A systemic review by Imam et al compared 7 cohort studies and found that there was a higher risk of dislocation occurrence after arthroscopic Bankart repair with a risk ratio of 2.87, however there was no difference in post-op complication rate. 75 Lastly, in a comparative study by Rai et al, authors reported a higher rate of functional satisfaction and a lower operating cost with the open Latarjet procedure compared to arthroscopic Bankart repair. 76 …”
Section: Open Latarjet Techniquementioning
confidence: 97%